THE GROWTH DYNAMICS OF ACHIEVEMENTS IN MATHEMATICS: ANALYSIS OF INTERNATIONAL REASEARCH - Šapkova, Aļesja (Acta Paedagogica Vilnensia, 2013)
Mathematics takes a specific place in the education of any country because the opportunities and success of youth in contemporary society are often dependent on their knowledge and skills exactly in the sphere of mathematics. Information about the status quo of mathematics education in a country is gained in an international comparative research on education. The goal of the present research is to reflect the results of the international project “Non-cognitive skills and Singapore learners – international comparison” organized by Singapore National Education Institute about the achievements of 2828 Latvian school learners of grade 9 in doing 12 mathematical sums. These results were compared with the Programme for International Student Assessment (PISA) 2003 research results this, in turn, made it possible to predict the results of the PISA 2012 research in teaching mathematics as well as to evaluate the efficiency of the new standard of education in Latvia in the first six years. The author also considers the causes of the low achievements of Latvian learners in doing sums in mathematics.
Keywords: learners’ achievements; mathematics education; international comparative research